Discourse Analysis on Announcement and Prohibition Board in the Province of Bangka Belitung Archipelago: The Study of Smart City - Saputra, Putra Pratama; Wijayanti, Nurvita; Wilujeng, Panggio Restu ((JELE) Journal Of English Language and Education, 2020)
Announcement board in the city is somehow disturbing because of the illogical linguistic rules therefore it does not support the development of the smart city.The banned boards are indicated to have less educative meaning because they contain elements of swearing, diatribe, bad prayer, and spelling and writing errors. The role of the government in this matter that is responsible for making writing standards and the contents of prohibition boards and notice boards must be in line with the standard rules of language. Therefore, the researcher wants to collaborate with the City Planning Office, which in this case is responsible for arranging the prohibition and announcement boards in the municipal, regency, and sub-district cities in the Bangka Belitung Islands Province. Therefore, the view of Sociology studies is needed to recommend the concept of an ecology city based on smart city. The research method used is mixed method, namely qualitative research conducted  by interviewing the local community and quantitative research by conducting a questionnaire and counting the prohibition boards and announcements that are indicated not in accordance with the language rules.